Oral Microbiota and Pediatric Asthma Phenotype: A New Window for Biomarkers? - Ghedin, Elodie; Huang, Yvonne J. (American journal of respiratory and critical care medicine, 2023)
Ghedin and Huang discuss the study by Abdel-Aziz et al analyzing the microbiota of oropharyngeal swabs collected from 241 children recruited with mild, moderate, or severe school-age asthma or preschool wheezing as part of a multicenter European observational cohort study (U-BIOPRED [Unbiased Biomarkers for the Prediction of Respiratory Disease Outcomes]). The authors hypothesized that although no differences in microbial diversity were previously found to be associated with disease severity in this dataset, there could be compositional differences that correlate with clinically relevant phenotypes.